PENGGUNAAN CAMPURAN PLASTIK DAN KACA KITAR SEMULA SEBAGAI AGREGAT GANTIAN DALAM CAMPURAN BERASFALT (Jurnal Teknologi (Sciences & Engineering), 2015)
The major problem in landfill is the large amount of solid wastes dumped in landfill. Waste plastics and glass contribute greatly to the problem and this needs to be managed in order to extend the life of landfill sites. Hence, this study was conducted to investigate the feasibility of using these waste materials in asphalt mixtures for pavement applications. The mixtures were designed by means of the Superior Performing Asphalt Pavements (Superpave) method. Various types of recycled waste plastics and glasses; namely bottle glass, LCD glass and sheet glass were selected in this study. Approximately 5% of recycled materials (by the total weight of asphalt mixtures) were used as an aggregate replacement. In this study, asphalt mixtures were aged in the laboratory to simulate the in-situ conditions of short-term and long-term ageing. After completion, samples were tested for resilient modulus, dynamic creep and static creep tests. It was found that replacements of 1% recycled plastics and 4% recycled glass show almost similar and satisfactory result compared to control sample for all tests. Consequently, recycled plastics and recycled glass, at their optimum blending, can be considered feasible to be used as an aggregate replacement in asphalt mixtures for road surfacing.Â Â